Land use, climate change and biodiversity modeling : perspectives and applications - Trisurat, Yongyut (Information Science Reference, 2015)
This book combines state-of-the-art modeling approaches at various scales with case studies from across the world, discussing how to translate models into results and illustrate how pro-active implementation can mitigate biodiversity loss.